2013
DOI: 10.1016/j.neuroimage.2013.04.085
|View full text |Cite
|
Sign up to set email alerts
|

The neural representation of sensorimotor transformations in a human perceptual decision making network

Abstract: Humans can quickly engage a neural network to transform complex visual stimuli into a motor response. Activity from a key region within this network, the intraparietal sulcus (IPS), has been associated with evidence accumulation and motor planning, thus implicating it in sensorimotor transformations. If such transformations occur within a brain region, a key and untested prediction is that neural activity reflecting both the parametric amount of evidence available and the timing of motor planning can be indepe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 42 publications
3
7
0
Order By: Relevance
“…In human observers, mechanisms of perceptual decision‐making have been investigated in several studies using functional magnetic resonance imaging (fMRI) and electroencephalography/magnetoencephalography methods (Heekeren et al ., ; Philiastides & Sajda, ; Ploran et al ., ; Tosoni et al ., ; Donner et al ., ; Ho et al ., ; Kayser et al ., ; Liu & Pleskac, ; Gould et al ., ; Hebart et al ., ; O'Connell et al ., ; Wyart et al ., ; Erickson & Kayser, ; Filimon et al ., ). Several studies have focused on the issue of whether perceptual decisions rely on response‐related mechanisms or are mediated by high‐level mechanisms independent of the motor response (Heekeren et al ., ; Ho et al ., ; Liu & Pleskac, ; Hebart et al ., ; O'Connell et al ., ; Filimon et al ., ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In human observers, mechanisms of perceptual decision‐making have been investigated in several studies using functional magnetic resonance imaging (fMRI) and electroencephalography/magnetoencephalography methods (Heekeren et al ., ; Philiastides & Sajda, ; Ploran et al ., ; Tosoni et al ., ; Donner et al ., ; Ho et al ., ; Kayser et al ., ; Liu & Pleskac, ; Gould et al ., ; Hebart et al ., ; O'Connell et al ., ; Wyart et al ., ; Erickson & Kayser, ; Filimon et al ., ). Several studies have focused on the issue of whether perceptual decisions rely on response‐related mechanisms or are mediated by high‐level mechanisms independent of the motor response (Heekeren et al ., ; Ho et al ., ; Liu & Pleskac, ; Hebart et al ., ; O'Connell et al ., ; Filimon et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have focused on the issue of whether perceptual decisions rely on response‐related mechanisms or are mediated by high‐level mechanisms independent of the motor response (Heekeren et al ., ; Ho et al ., ; Liu & Pleskac, ; Hebart et al ., ; O'Connell et al ., ; Filimon et al ., ). Some evidence (Tosoni et al ., ; Donner et al ., ; Gould et al ., ; Erickson & Kayser, ) indicates that perceptual decision‐related signals occur in regions involved in planning and executing actions consistently with the intentional framework, but the slow temporal resolution of the blood‐oxygenation‐level‐dependent (BOLD) signal has prevented a clear separation of decision from motor planning signals.…”
Section: Introductionmentioning
confidence: 99%
“…On any given trial, the level of noise, or stimulus evidence, was varied randomly. The task itself, as well as similar visual decision-making tasks 28 , is believed to engage an extensive set of cortical areas in a coordinated fashion, including regions that are responsible for sensory encoding, evidence accumulation, decision formation, and response and decision monitoring. However, the dynamic interplay of these regions has never been observed in humans.…”
Section: Resultsmentioning
confidence: 99%
“…Using a mathematical framework, it has been demonstrated that the anterior areas of prefrontal cortex are involved in making more complex decisions (24). An attempt for modeling the human cognitive procedures has been recently made through the simulated processes like acquired rule-based systems or manipulation of visual representations in decision-making (25). Computational modeling of cognitive functions has revealed that information from multiple sensory modalities are integrated in the frontal and parietal lobes of the brain (26,27).…”
Section: Application Of Computational Models In Decision-making and Pmentioning
confidence: 99%